2014
DOI: 10.1039/c4cy00738g
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienyl molybdenum alkyl ester complexes as catalyst precursors for olefin epoxidation

Abstract: New molybdenum complexes of the type [CpMo(CO) 3 X] containing ligands of the formula X = CHR 2 CO(OR 1 )where R 1 = ethyl (1), menthyl (4), and bornyl (5) and R 2 = H; R 1 = ethyl and R 2 = methyl (2) and phenyl (3) have been synthesized and characterized by NMR and IR spectroscopy and X-ray crystallography.These compounds have been applied as catalyst precursors for achiral and chiral epoxidation of unfunctionalized olefins with tert-butyl hydroperoxide (TBHP) as the oxidant at 22°C (in CH 2 Cl 2 ) and 55°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…It is also found that no precipitate forms during catalytic epoxidation with complexes 1 and 5-8 (Section 3.5 and Ref. [38]). Formation of a precipitate during catalytic epoxidation of alkenes with similar Mo-based complexes has also been reported, but the nature of the precipitate has remained elusive [10,28,[44][45][46][47].…”
Section: Formation Of Precipitate On Oxidation Of 5 With Tbhpmentioning
confidence: 92%
See 4 more Smart Citations
“…It is also found that no precipitate forms during catalytic epoxidation with complexes 1 and 5-8 (Section 3.5 and Ref. [38]). Formation of a precipitate during catalytic epoxidation of alkenes with similar Mo-based complexes has also been reported, but the nature of the precipitate has remained elusive [10,28,[44][45][46][47].…”
Section: Formation Of Precipitate On Oxidation Of 5 With Tbhpmentioning
confidence: 92%
“…Complexes 1-5 [38,39], 6 [40,41], 7 and 8 [39,41] were prepared by known methods. All NMR experiments were carried out in CDCl 3 solvent under ambient conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations